Anxiety and Depression among Pregnant Women and Mothers of Children Under one Year in Sindupalchowk District - Aryal, Krishna Kumar; Alvik, Astrid; Thapa, Narbada; Mehata, Suresh; Roka, Tara; Thapa, Pushpa; Pandey, Pragya; Pedersen, Babill Stray (Journal of Nepal Health Research Council, 2018)
Background: Common mental disorders such as anxiety and depression among mothers of young children and expectants can silently deteriorate the health of the mother with significant impact on the newborn. The primary aims were to determine the proportion of pregnant women and mothers of children under one year with anxiety and depression and their associated factors in Sindhupalchowk.Methods: We used the Hopkins Symptom Checklist 25 and a structured questionnaire in a cross-sectional study to collect information from 778 women (164 pregnant women, 614 mothers of children under one year) selected through multi-stage sampling. Results: Among pregnant women, the study found that 21.3%(95%CI:15.7–28.3) had anxiety and 23.8% (95%CI:17.8–31.0) had depression. Being from the Dalit ethnic group was independently associated with anxiety and depression. Among mothers of children under one year, 18.7% (95%CI:15.7–22.1) had anxiety and 15.2% (95%CI:12.4–18.4) had depression. Among these women, low education level; primary source of family income being agriculture, animal husbandry or labour; history of unplanned pregnancy; and use of tobacco were independently associated with anxiety and history of unplanned pregnancy and use of tobacco were independently associated with depression.Conclusions: A substantial proportion of women had anxiety and depression with higher odds of anxiety and depression in certain group of women. Targeted health system interventions are needed for improving the psychological well being of women, including pregnant women, as well as newborn health and wellbeing.Keywords: Anxiety; depression; mothers of children under one year; Nepal; pregnant women.